PENGARUH KENAKALAN REMAJA TERHDAP HASIL BELAJAR MATA PELAJARAN PPKN SISWA KELAS XI SMA NEGERI 2 TAPUNG KABUPATEN KAMPAR - Sari, Ani yulita; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the rampant juvenile delinquency that occurs at school. Juvenile delinquency at school age is very vulnerable to occur because students are still looking for their true identity and are very easily influenced by the community environment. As for the title of the study